Fodder productivity and nutritional value of sorghum (Sorghum bicolor) as influenced by seeding rate and harvesting time - NIKHIL; KAUR, MANINDER; OBEROI, HARPREET KAUR; SINGH, RAJBIR; SINGH, SOMPAL (The Indian Journal of Agricultural Sciences, 2026)
The experiment was conducted during rainy (kharif) seasons of 2023 and 2024 at Forage Research Farm, Punjab Agricultural University, Ludhiana, Punjab to investigate the effects of varying seeding rates (25, 37.5, 50, 62.5 and 75 kg/ha) and two harvesting times (booting and flowering stage) on the fodder productivity and nutritional quality of sorghum [Sorghum bicolor (L.) Moench]. Results revealed that the increase in seeding rate would significantly increase the emergence count, plant height and leaf area index. Moreover, leaf stem ratio, dry matter accumulation and crude protein were significantly highest with seed rates of 50–62.5 kg/ha being at par with 37.5 kg/ha. Significant increase in green fodder yield was recorded only up to 37.5 kg/ha over the lowest seeding rate of 25 kg/ha, further increase in seed rate beyond 37.5 kg/ha brought only a marginal increase in yield up to 62.5 kg/ha and a slight decline in yield with 75 kg/ha. Harvesting at flowering stage obtained significant increase of 10.8 % in green fodder yield with appreciable quality over the booting stage. A seeding rate of 37.5–50 kg/ha optimised plant population and resource use, achieving the highest net returns and B:C ratio. Thus, the results indicated that production input of seed can be reduced without negative effects on performance of variety SL-46 high biomass producing and late maturing variety and harvest at flowering stage (80–85 DAS) is recommended to achieve higher yield and satisfactory nutritional quality.